KONEKTIVITAS KEBUDAYAAN INDIA DAN JAWA ABAD PERTAMA HINGGA KE-10 MASEHI - Ridwan, Sinta; Winardi, Donny; Sunaryo, Hary; Munandar, Agus Aris (Multikultura, 2026)
This article analyses the cultural connectivity between India and Java from the first century to the tenth century CE. The primary method employed is chronological synchronisation, namely the alignment of political events in India with the emergence and development of kingdoms in Java, combined with a multidisciplinary approach drawing on epigraphic, archaeological, and historical data. The analysis identifies four stages of connectivity. The earliest stage, spanning the first to the third century CE, is marked by maritime trade and early encounters between Austronesian sailors and Indian traders, evidenced by Indian Rouletted Ware pottery found in the Buni cultural complex and at Sembiran. The next stage, from the fourth to the sixth century CE, corresponds to the decline of the Gupta Empire following Hūṇa invasions and the rise of the Tārumānagara Kingdom in western Java under King Pūrṇawarman. The following stage, from the seventh to the eighth century CE, is characterised by the Pallava-Cālukya rivalry in South India alongside the growth of the Holing Kingdom and religious architecture on the Dieng Plateau and its surroundings. The culminating stage, from the ninth to the tenth century CE, demonstrates reciprocal relations between the Pala Dynasty in Bengal and the Sailendra Dynasty in Java, evidenced by the Nālandā Copper-Plate that records the construction of a Buddhist monastery by Maharaja Balaputradeva in the Nālandā complex with the support of King Devapaladeva. This study argues that political dynamics on the Indian subcontinent constituted a push factor for elite migration to Java, while local communities played an active role as both recipients and developers of Indian cultural elements. At its peak, the India-Java relationship evolved into a reversed flow in the form of religious patronage from Java to India, demonstrating that this connectivity was not a one-way relationship but rather a mutually enriching dialogue of cultures.